Mercury Isotopes Track the Causes of Carbon Perturbations in the Early Permian Ocean and Continent - Fang, Qiang; Wu, Huaichun; Chen, Jiubin; Grasby, Stephen E.; Zheng, Wang; Shen, Shu‐zhong; Huang, Wentao; Xu, Junjie; Zhang, Shihong (Geophysical research letters, 2025)
The Early Permian witnessed the first icehouse‐to‐greenhouse turnover of the vegetated Earth, yet its climate dynamics remain enigmatic. Here, we used mercury (Hg) isotopes from pelagic and continental successions at low paleo‐latitudes to track the perturbations of the global carbon (C) cycle and the climatic impact. Our results indicate that small‐scale volcanism promoted marine organic C burial, and the concomitant extreme cooling triggered the waning of wetland ecosystems in North China block at ∼296.2 Ma. Subsequently, the mass‐independent fractionation of odd Hg isotopes (Δ199Hg) and C isotopes synchronously decline in the deep‐marine succession, likely supporting progressive oxidation of terrestrial biomass and airborne release of Hg and C. Lowered C sequestration (as coal swamps) on land and dampened continental weathering limited the drawdown of CO2 emissions from wildfires, initiating deglaciation. Our findings highlight that the climate forcing on terrestrial ecosystems could activate additional C reservoirs, driving Earth into a warmer state. Plain Language Summary We tracked the causes of global carbon perturbation during the onset of the demise of the Late Paleozoic Ice Age using Hg concentration and isotope data from low‐latitude marine and continental successions. Our study indicates that small‐scale volcanic activity facilitated marine organic carbon burial, and that the concomitant cooling pulse promoted the waning of tropical wetland ecosystem at ∼296.2 Ma. Subsequently, oxidation of terrestrial biomass and airborne release of Hg and C resulted in decreased mass‐independent fractionation of odd Hg isotopes (Δ199Hg) and carbon isotopes in the deep‐marine succession. Lowered terrestrial C sequestration and continental weathering limited the drawdown of the CO2 emissions from wildfires, acting as the important forcing of global warming and deglaciation during the early Permian. Key Points Small‐scale volcanic activity mediated the carbon perturbation at the apex of the Late Paleozoic Ice Age Extreme cooling promoted the waning of tropical wetland ecosystems at 296.2 Ma CO2 emissions from wildfires may play an important role in the deglaciation event beginning at ~294 Ma